Modified polyacrylonitrile fiber as well as preparation method and application thereof
Through the use of heavy objects to fix fiber and heating reactions in hydroxylamine solutions during the modification of polypropylene fiber, it solves the problem of fiber contraction and entanglement, and realizes efficient modification and improving uranium adsorption capacity.
Patent Information
- Application Number
- CN202411633886.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-15
- Publication Date
- 2025-01-28
AI Technical Summary
During the process of modifying polyacrylonitrile fibers, the fibers are prone to shrink and wrap, resulting in uneven modification effects and significantly reducing the modification effect of the fibers.
By bundling the polypropylene fiber at one end and fix it around the heavy objects, and heated the hydroxyine solution, the fiber stretchs in the direction of gravity, increases the modified ratio and shorten the modification reaction time.
The efficient modification of polypropylene fiber is achieved, the proportion of modification is improved, the reaction time of the modification is shortened, and the uranium adsorption ability of the fiber is improved.
Smart Images

Figure CN119372913A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to modified polyacrylonitrile fiber and a preparation method and application thereof. Background Art
[0002] There are huge reserves of uranium resources in seawater, and the research on uranium extraction from seawater has good application prospects for the utilization of marine mineral resources. Uranium-containing wastewater is produced during the nuclear industry production process, and enriching and recycling the uranium in it is not only environmentally friendly, but also has good economic value.
[0003] In the field of uranium recovery and utilization in water, amidoxime-modified adsorbent materials are widely used and have good adsorption effects. Amidoxime-based adsorbent materials are mostly obtained by modifying polyacrylonitrile polymer materials, or by grafting cyano groups onto polymer skeletons and then reacting with hydroxylamine.
[0004] Polyacrylonitrile fiber, also known as acrylic fiber, is a widely used industrial fiber material. Using polyacrylonitrile fiber as raw material for hydroxylamine modification to obtain amidoxime-based adsorption material is an application approach to obtain uranium adsorption functional fiber. However, during the modification process of polyacrylonitrile fiber, as the degree of modification increases, the fiber gradually shrinks. In addition, due to the difference in the degree of modification at different positions of the polyacrylonitrile fiber, the degree of shrinkage is inconsistent, resulting in entanglement and entanglement of the polyacrylonitrile fiber. As the degree of modification deepens, the shrinkage and entanglement of the polyacrylonitrile fiber become more serious, resulting in the polyacrylonitrile fiber wrapped in the middle being isolated from the reaction solution, resulting in a huge difference in the degree of modification inside and outside the fiber, which significantly reduces the modification effect of the fiber. Summary of the invention
[0005] In view of this, one object of the present invention is to provide a method for preparing modified polyacrylonitrile fiber. The method can realize the reverse stretching of polyacrylonitrile fiber in the direction of gravity in the reaction solution, increase the modification ratio of polyacrylonitrile fiber and shorten the modification reaction time. Another object of the present invention is to provide modified polyacrylonitrile fiber prepared by the above preparation method. Another object of the present invention is to provide the use of the above modified polyacrylonitrile fiber.
[0006] The present invention adopts the following technical solutions to achieve the above-mentioned purpose.
[0007] In one aspect, the present invention provides a method for preparing modified polyacrylonitrile fiber, comprising the following steps:
[0008] 1) tying and fixing one end of the polyacrylonitrile fiber around a weight to form a polyacrylonitrile fiber counterweight; the mass ratio of the weight to the polyacrylonitrile fiber is 2:1 to 6:1;
[0009] 2) immersing the polyacrylonitrile fiber weight in a hydroxylamine solution to form a reaction mixture; wherein the solvent of the hydroxylamine solution is a mixture of C1-C5 alkyl alcohol and water; the molar ratio of the polyacrylonitrile fiber to the hydroxylamine is 1:2-1:15; and the pH value of the hydroxylamine solution is 6.5-7.5;
[0010] 3) The reaction mixture is heated to 50-80° C. and reacted at 50-80° C. for 2-10 hours to obtain modified polyacrylonitrile fiber.
[0011] According to the preparation method of the present invention, preferably, in step 1), the length of a single polyacrylonitrile fiber is 10 to 120 cm; more preferably, 50 to 100 cm.
[0012] According to one embodiment of the present invention, the mass ratio of the weight to the polyacrylonitrile fiber is preferably 3:1 to 5:1.
[0013] In step 1) of the present invention, the density of the weight needs to be greater than the density of the hydroxylamine solution to ensure that the weight can sink in the hydroxylamine solution.
[0014] According to the preparation method of the present invention, preferably, in step 1), the weight is selected from one or more of the following materials:
[0015] (1) Polytetrafluoroethylene;
[0016] (2) Metal encapsulated by polytetrafluoroethylene;
[0017] (3) Non-metal wrapped by polytetrafluoroethylene.
[0018] More preferably, the weight is polytetrafluoroethylene or polytetrafluoroethylene-wrapped metal.
[0019] According to the preparation method of the present invention, preferably, the metal is selected from at least one of iron and lead, and more preferably iron or lead. The non-metal is selected from at least one of cement, glass, stone, and coal, and more preferably cement, glass, stone, and coal. The stone can be any material known in the art.
[0020] In the present invention, in order to ensure the stability of the reaction system and avoid the introduction of impurities, polytetrafluoroethylene needs to completely wrap the metal or non-metal to prevent the metal or non-metal from contacting the hydroxylamine solution.
[0021] In step 1), one end of the polyacrylonitrile fiber is tied and fixed around the weight, which can be done by utilizing the linearity of the polyacrylonitrile fiber itself. One end of the polyacrylonitrile fiber can also be tied and fixed around the weight using a string or a ring with a stable material. The material of the string or ring used can be selected from one of nylon, aramid, polytetrafluoroethylene, silicone, polyester, and fluororubber; preferably one of nylon, aramid, polytetrafluoroethylene, and silicone; more preferably one of nylon, aramid, and polytetrafluoroethylene.
[0022] In step 1), one end of the polyacrylonitrile fiber is tied and fixed around a weight, and the weight ratio of the weight to the polyacrylonitrile fiber is controlled within the above range, which can ensure that the polyacrylonitrile fiber stretches in the direction opposite to the direction of gravity in the reaction solution, so that the polyacrylonitrile fiber presents a "seaweed-like" bionic state, which is beneficial to the modification of the polyacrylonitrile fiber and is more beneficial to shortening the modification reaction time of the polyacrylonitrile fiber.
[0023] According to one embodiment of the present invention, in step 2), the molar ratio of the polyacrylonitrile fiber to hydroxylamine is preferably 1:3 to 1:12.
[0024] According to one embodiment of the present invention, in step 2), the pH value of the hydroxylamine solution is preferably 6.8 to 7.2; more preferably 6.9 to 7.1.
[0025] According to another embodiment of the present invention, an alkali metal hydroxide is used to adjust the pH value of the hydroxylamine solution. The alkali metal hydroxide is selected from at least one of sodium hydroxide and potassium hydroxide; preferably sodium hydroxide or potassium hydroxide. The alkali metal hydroxide can be added directly in the form of solid powder or prepared as a solution, which is not limited here.
[0026] According to the preparation method of the present invention, preferably, in step 2), the molar concentration of hydroxylamine in the hydroxylamine solution is 12 to 60 mmol / L; more preferably 15 to 58 mmol / L.
[0027] According to the preparation method of the present invention, preferably, in step 2), the hydroxylamine of the hydroxylamine solution comes from hydroxylamine hydrochloride or hydroxylamine sulfate. Hydroxylamine hydrochloride contains one hydroxylamine, and hydroxylamine sulfate contains two hydroxylamines. The molar concentration of hydroxylamine in the hydroxylamine solution represents the molar concentration of hydroxylamine in the solution.
[0028] According to the preparation method of the present invention, preferably, in step 2), in the mixed solution of C1-C5 alkyl alcohol and water, the volume ratio of C1-C5 alkyl alcohol to water is 1:0.5-1:2; more preferably 1:0.8-1:1.5. The water can be deionized water or ultrapure water, more preferably deionized water. The use of a reasonable solvent is conducive to the oximation reaction, increasing the modification ratio of polyacrylonitrile fiber, and more conducive to improving the uranium adsorption capacity of polyacrylonitrile fiber.
[0029] According to the preparation method of the present invention, preferably, in step 2), the C1-C5 alkyl alcohol is a C1-C3 normal alkyl alcohol; more preferably, the C1-C3 normal alkyl alcohol is methanol or ethanol.
[0030] In step 2), controlling the ratio of the reaction raw materials within the above range is beneficial to the oximation reaction and is more beneficial to the amidoxime modification of the polyacrylonitrile fiber.
[0031] According to the preparation method of the present invention, in step 3), the reaction temperature is preferably 60 to 75° C. The reaction time is preferably 5 to 9 hours.
[0032] According to one embodiment of the present invention, in step 3), the polyacrylonitrile fiber is kept stretched in the hydroxylamine solution in the opposite direction of gravity during the reaction process, presenting a "seaweed-like" bionic state.
[0033] According to one embodiment of the present invention, in step 3), after reacting for 0.5 to 2 hours, the fiber begins to gradually shrink. After reacting for another 0.5 to 2 hours, the fiber no longer shrinks. Then, the reaction is continued for 1 to 8 hours to obtain modified polyacrylonitrile fiber.
[0034] In step 3), controlling the reaction conditions within the above range is beneficial to the oximation reaction and is more beneficial to the amidoxime modification of the polyacrylonitrile fiber.
[0035] On the other hand, the present invention also provides modified polyacrylonitrile fiber prepared by the above preparation method. The amidoxime modification ratio of the modified polyacrylonitrile fiber can be above 90%.
[0036] The adsorption capacity of the modified polyacrylonitrile fiber for uranium in natural seawater can be 1.2 mg / g or more, preferably 1.4 mg / g or more. The adsorption capacity of the modified polyacrylonitrile fiber for uranium in uranium-containing industrial wastewater can be 30 mg / g or more, preferably 35 mg / g or more.
[0037] On the other hand, the present invention also provides the use of the modified polyacrylonitrile fiber in extracting uranium from a uranium-containing solution.
[0038] According to the use of the present invention, preferably, the uranium-containing solution is selected from at least one of natural seawater and uranium-containing industrial wastewater; more preferably, it is natural seawater or uranium-containing industrial wastewater.
[0039] The invention loads the polyacrylonitrile fiber on a weight, so that the polyacrylonitrile fiber can stretch in the reaction solution in the reverse direction of gravity, thereby increasing the modification ratio of the polyacrylonitrile fiber and shortening the modification reaction time of the polyacrylonitrile fiber. BRIEF DESCRIPTION OF THE DRAWINGS
[0040] Figure 1 The modified polyacrylonitrile fiber prepared in Example 1 of the present invention;
[0041] Figure 2 This is the modified polyacrylonitrile fiber prepared in Comparative Example 2 of the present invention. DETAILED DESCRIPTION
[0042] The present invention is further described below in conjunction with specific embodiments, but the protection scope of the present invention is not limited thereto.
[0043] The "uranium adsorption capacity" mentioned in the present invention refers to the amount of uranium adsorbed by a unit adsorbent, and the unit is mg / g.
[0044] <Ingredients>
[0045] Unless otherwise specified, the raw materials used in the following examples are all commercially available products.
[0046] <Test Method>
[0047] Adsorption experiment (1)
[0048] 10g of activated modified polyacrylonitrile fiber was weighed and loaded into a porous water-permeable bag. The porous water-permeable bag containing modified polyacrylonitrile fiber was immersed in natural seawater (uranium concentration was 3.3μg / L) in the South China Sea region to allow the modified polyacrylonitrile fiber to adsorb uranium in natural seawater. The average temperature of the seawater during the experiment was 25°C. After 30 days of adsorption, the uranium adsorption capacity of the modified polyacrylonitrile fiber was measured.
[0049] Adsorption experiment (2)
[0050] Take 5.0L of uranium-containing industrial wastewater. In the uranium-containing industrial wastewater, the uranium content is 3.5mg / L, the sodium ion concentration is 10.5mg / L, the magnesium ion concentration is 1.3mg / L, the sulfate concentration is 0.03mol / L, the bicarbonate concentration is 0.01mol / L, and the chloride ion concentration is 0.55mol / L. Weigh 0.2g of the activated modified polyacrylonitrile fiber, immerse it in the nuclear industry uranium-containing wastewater, shake it on a shaker at room temperature (25℃) for 48 hours, and measure the uranium adsorption capacity of the modified polyacrylonitrile fiber.
[0051] Determination of uranium content
[0052] The uranium content was determined using an Agilent 8900 inductively coupled plasma mass spectrometer (ICP-MS).
[0053] Example 1
[0054] (1) Take 100 g of polyacrylonitrile fiber and cut it into a single fiber sample with a length of 50 cm. Tie one end of the fiber sample around a 300 g iron block weight completely wrapped with polytetrafluoroethylene to obtain a polyacrylonitrile fiber counterweight.
[0055] (2) Weigh 390 g of hydroxylamine hydrochloride, dissolve it in 13 L of a mixed solvent of methanol and water (the volume ratio of methanol to water is 1:1), and stir it thoroughly until it is completely dissolved to prepare a hydroxylamine solution with a molar concentration of 43.17 mmol / L. Slowly add sodium hydroxide powder to neutralize the pH value of the hydroxylamine solution to neutral (pH = 7.0).
[0056] (3) Immersing the polyacrylonitrile fiber weight in the neutralized hydroxylamine solution to form a reaction mixture. The molar ratio of the polyacrylonitrile fiber to the hydroxylamine is 1:3.09, and the polyacrylonitrile fiber maintains reverse stretching along the direction of gravity in the hydroxylamine solution.
[0057] (4) The reaction mixture is heated to 75° C. and reacted at 75° C. to ensure that the polyacrylonitrile fiber stretches in the solution in the opposite direction of gravity during the reaction, presenting a "seaweed-like" biomimetic state. After reacting for 1.5 hours, the fiber begins to shrink gradually. After reacting for another 1.5 hours, the fiber no longer shrinks. The reaction is then continued for 6 hours to obtain modified polyacrylonitrile fiber.
[0058] After the reaction, the modified polyacrylonitrile fiber was washed three times with deionized water, and then dried in a vacuum oven at 45°C for 24 hours. Figure 1 As shown. The fiber modification ratio is calculated based on the dry weight of polyacrylonitrile fiber before and after the reaction. The formula is as follows:
[0059]
[0060] In the formula: m0 is the dry weight of the polyacrylonitrile fiber before the reaction; m1 is the dry weight of the modified polyacrylonitrile fiber after the reaction; DG is the modification ratio; 53 is the relative molecular mass of the single block (C3H3N) of the polyacrylonitrile fiber; 33 is the difference between the relative molecular mass (86) of the amidoxime group (C3H6N2O) and the relative molecular mass (53) of the single block (C3H3N) of the polyacrylonitrile fiber.
[0061] According to measurement and calculation, the modification ratio of the modified polyacrylonitrile fiber prepared in this embodiment is 91%. The present invention realizes the amidoximation modification of polyacrylonitrile fiber at a relatively high ratio.
[0062] Example 2
[0063] (1) Take 40g of polyacrylonitrile fiber and cut it into a single fiber sample with a length of 90cm. Tie one end of the fiber sample around a 200g iron block weight completely wrapped with polytetrafluoroethylene to obtain a polyacrylonitrile fiber counterweight.
[0064] (2) Weigh 390 g of hydroxylamine hydrochloride, dissolve it in 13 L of a mixed solvent of methanol and water (methanol to water volume ratio is 1:1), stir thoroughly until completely dissolved, and prepare a hydroxylamine solution with a molar concentration of 57.55 mmol / L. Measure the pH value of the hydroxylamine solution, slowly add sodium hydroxide powder, and neutralize the pH value of the hydroxylamine solution to neutral (pH = 7.0).
[0065] (3) Immersing the polyacrylonitrile fiber weight in the neutralized hydroxylamine solution to form a reaction mixture. The molar ratio of the polyacrylonitrile fiber to the hydroxylamine is 1:10.28, and the polyacrylonitrile fiber maintains reverse stretching along the gravity direction in the hydroxylamine solution.
[0066] (4) The reaction mixture is heated to 70° C. and reacted at 70° C. to ensure that the polyacrylonitrile fiber stretches in the solution in the opposite direction of gravity during the reaction, presenting a "seaweed-like" biomimetic state. After one hour of reaction, the fiber begins to gradually shrink. After another 1.5 hours of reaction, the fiber no longer shrinks. The reaction is then continued for 6 hours to obtain modified polyacrylonitrile fiber.
[0067] After the reaction was completed, the modified polyacrylonitrile fiber was washed three times with deionized water, and then dried in a vacuum oven at 45° C. for 24 hours. The fiber modification ratio was calculated based on the fiber dry weight before and after the reaction, and the calculation formula was the same as in Example 1.
[0068] According to measurement and calculation, the modification ratio of the modified polyacrylonitrile fiber prepared in this embodiment is 96%. The present invention realizes the amidoximation modification of polyacrylonitrile fiber at a relatively high ratio.
[0069] Comparative Example 1
[0070] (1) Take 20 g of dry weight of polyacrylonitrile fiber and cut it into a single fiber sample with a length of 60 cm. Tie one end of the fiber sample around a 90 g polytetrafluoroethylene weight to obtain a polyacrylonitrile fiber counterweight.
[0071] (2) Weigh 200 g of hydroxylamine hydrochloride, dissolve it in 8 L of deionized water, and stir it thoroughly until it is completely dissolved to prepare a hydroxylamine solution with a molar concentration of 35.98 mmol / L. Slowly add sodium hydroxide powder to neutralize the pH value of the hydroxylamine solution to neutral (pH = 7.0).
[0072] (3) Immersing the polyacrylonitrile fiber weight in the neutralized hydroxylamine solution to form a reaction mixture. The molar ratio of the polyacrylonitrile fiber to the hydroxylamine is 1:7.91, and the polyacrylonitrile fiber maintains reverse stretching along the direction of gravity in the hydroxylamine solution.
[0073] (4) The reaction mixture is heated to 75°C and reacted at 75°C to ensure that the polyacrylonitrile fiber stretches in the solution in the opposite direction of gravity during the reaction, presenting a "seaweed-like" biomimetic state. After reacting for 3 hours, the fiber begins to shrink gradually. After reacting for another 1.5 hours, the polyacrylonitrile fiber no longer shrinks. The reaction is then continued for 4 hours to obtain modified polyacrylonitrile fiber.
[0074] After the reaction was completed, the modified polyacrylonitrile fiber was washed three times with deionized water, and then dried in a vacuum oven at 45° C. for 24 hours. The fiber modification ratio was calculated based on the fiber dry weight before and after the reaction, and the calculation formula was the same as in Example 1.
[0075] After measurement and calculation, the modification ratio of the modified polyacrylonitrile fiber prepared in this comparative example is only 73%. Compared with Example 1 and Example 2, in the case of no methanol in the reaction solution, the modification ratio of the modified polyacrylonitrile fiber prepared in this comparative example is significantly reduced.
[0076] Comparative Example 2
[0077] (1) Weigh 390 g of hydroxylamine hydrochloride, dissolve it in 13 L of a mixed solvent of methanol and water (the volume ratio of methanol to water is 1:1), and stir it thoroughly until it is completely dissolved to prepare a hydroxylamine solution with a molar concentration of 43.17 mmol / L. Slowly add sodium hydroxide powder to neutralize the pH value of the hydroxylamine solution to neutral (pH = 7.0).
[0078] (2) 100 g of polyacrylonitrile fiber is completely immersed in the neutralized hydroxylamine solution to form a reaction mixture. The molar ratio of the polyacrylonitrile fiber to the hydroxylamine is 1:3.09.
[0079] (3) The reaction mixture was heated to 75°C and reacted at 75°C. After 6 hours of reaction, the fibers began to gradually shrink and agglomerate. The reaction was continued for 2 hours, and the fibers not wrapped on the outside stopped shrinking. The reaction was then continued for 22 hours to allow the fibers wrapped inside to complete the reaction, and finally modified polyacrylonitrile fibers were obtained.
[0080] After the reaction, the modified polyacrylonitrile fiber was washed three times with deionized water, and then dried in a vacuum oven at 45°C for 24 hours. Figure 2 The fiber modification ratio is calculated based on the fiber dry weight before and after the reaction, and the calculation formula is the same as that in Example 1.
[0081] After measurement and calculation, the modification ratio of the modified polyacrylonitrile fiber prepared in this comparative example is only 53%. Compared with Example 1 and Example 2, the modification ratio of the modified polyacrylonitrile fiber prepared in this comparative example is significantly reduced and the reaction time is significantly increased, and the prepared modified polyacrylonitrile fiber is seriously agglomerated compared with Example 1.
[0082] Experimental Example 1
[0083] The modified polyacrylonitrile fibers prepared in Example 1, Example 2, Comparative Example 1 and Comparative Example 2 were immersed in a sodium hydroxide solution having a mass concentration of 0.5 wt %, and heated at 40° C. for 3 h for alkali activation. After alkali activation, the modified polyacrylonitrile fibers were washed three times with deionized water. Adsorption experiments (1) and (2) were performed using the activated modified polyacrylonitrile fibers to verify the adsorption capacity of uranium in water. The experimental results are shown in Table 1.
[0084] Table 1
[0085]
[0086] As shown in Table 1, the modified polyacrylonitrile fiber prepared by the present invention has good adsorption capacity for uranium in natural seawater and uranium-containing industrial wastewater. It can show good application effects in the fields of uranium extraction from seawater and uranium removal from uranium-containing industrial wastewater. However, the uranium adsorption capacity of Comparative Examples 1 and 2 is relatively poor.
[0087] The present invention is not limited to the above-mentioned embodiments. Without departing from the essential content of the present invention, any deformation, improvement and substitution that can be conceived by those skilled in the art shall fall within the scope of the present invention.
Claims
1. A method for preparing modified polyacrylonitrile fiber, comprising the following steps: 1) tying and fixing one end of the polyacrylonitrile fiber around a weight to form a polyacrylonitrile fiber counterweight; the mass ratio of the weight to the polyacrylonitrile fiber is 2:1 to 6:1; 2) immersing the polyacrylonitrile fiber weight in a hydroxylamine solution to form a reaction mixture; wherein the solvent of the hydroxylamine solution is a mixture of C1-C5 alkyl alcohol and water; the molar ratio of the polyacrylonitrile fiber to the hydroxylamine in the reaction mixture is 1:2-1:15; and the pH value of the hydroxylamine solution is 6.5-7.5; 3) The reaction mixture is heated to 50-80° C. and reacted at 50-80° C. for 2-10 hours to obtain modified polyacrylonitrile fiber.
2. The preparation method according to claim 1, characterized in that: In step 1), the length of a single piece of polyacrylonitrile fiber is 10 to 120 cm.
3. The preparation method according to claim 1, characterized in that: In step 1), the weight is selected from one or more of the following materials: (1) Polytetrafluoroethylene; (2) Metal encapsulated by polytetrafluoroethylene; (3) Non-metal wrapped by polytetrafluoroethylene.
4. The preparation method according to claim 1, characterized in that: In step 2), the molar concentration of hydroxylamine in the hydroxylamine solution is 12 to 60 mmol / L.
5. The preparation method according to claim 1, characterized in that: In step 2), the hydroxylamine in the hydroxylamine solution comes from hydroxylamine hydrochloride or hydroxylamine sulfate.
6. The preparation method according to claim 1, characterized in that: In step 2), the volume ratio of the C1-C5 alkyl alcohol to water is 1:0.5 to 1:
2.
7. The preparation method according to claim 1, characterized in that: In step 2), the C1-C5 alkyl alcohol is a C1-C3 normal alkyl alcohol.
8. The preparation method according to claim 7, characterized in that: In step 2), the C1-C3 n-alkyl alcohol is methanol or ethanol.
9. The modified polyacrylonitrile fiber prepared by the preparation method according to any one of claims 1 to 8, characterized in that: The amidoxime modification ratio of the modified polyacrylonitrile fiber is more than 90%; The modified polyacrylonitrile fiber has an adsorption capacity of 1.2 mg / g or more for uranium in natural seawater and an adsorption capacity of 30 mg / g or more for uranium in uranium-containing industrial wastewater.
10. Use of the modified polyacrylonitrile fiber according to claim 9 in extracting uranium from a uranium-containing solution.
Citation Information
Cited By
Development of a new heavy-metal-adsorbing material based on modified technical textile fiber waste
MA70871A1